Target Zones and Realignment Expectations : The Israeli and Mexican Experience - Werner, Alejandro (IMF Working Papers; Working Paper, 1995)
This paper studies the Mexican and Israeli experience with a target zone. The first part of the paper develops a model of exchange rate determination under a target zone regime with stochastic realignments, and examines the conditions under which the adoption of the target zone, instead of a fixed exchange rate, reduces the volatility of the interest rate differential. We conclude that if the variance of the expected realignment is sufficiently large, then the target zone will be useful. The second part of the paper is an empirical study that shows that the target zone regime helped reduce interest rate variability in Israel and Mexico by absorbing part of the shocks to the expected realignment with movements of the exchange rate inside the band.